Âmes sensibles s’abstenir : violence à / de l’art contemporain - Catherine Bernard (Sillages Critiques)
The representation of violence has been central to the history of western art. Modern and contemporary art seems, for its part, to turn violence against art itself in a critical gesture that engages our aesthetic relation and seems to exhaust meaning. The present article explores the way some of the leading figures of contemporary British art have appropriated that debate in order to imagine and embody a new pragmatics of art. While building on the history of conceptual avant-garde, they force the spectator to a radical experience in which the shock of sensation and experience generates a moment of critical sublation. The confrontation with the work produces a form of « productive paradox » which turns sensation into intelligence.